Long-term Neurotoxic Effects of Early-life Exposure to Tetrachloroethylene-contaminated Drinking Water - Ann Aschengrau (Ubiquity Press, 2016)
Background: Tetrachloroethene (PCE) is a common environmental and occupational contaminant and an acknowledged neurotoxicant. From 1968 through 1983, widespread contamination of public drinking water supplies with PCE occurred in the Cape Cod region of Massachusetts. The source of the contamination was a vinyl liner applied to the inner surface of water distributionpipes. Objectives: A retrospective cohort study (the Cape Cod Health Study) was undertaken to examine possible health consequences of early-life exposure to PCE-contaminated drinking water. This review describes the study methods and findings regarding the effects of prenatal and childhood exposure on neurologic outcomes during early adulthood, including vision, neuropsychological functioning, brain structure, risky behaviors, and mental illness. The review also describes the strengths and challenges of conducting population-based epidemiologic research in this unique setting. Methods: Participants were identified by cross-matching birth certificates and water system data. Information on health outcomes and confounding variables was collected from self-administered surveys (n = 1689), neuropsychological tests (n = 63), vision examinations (n = 63), and magnetic resonance imaging (n = 42). Early-life exposure to PCE was estimated using a leaching and transport model. The data analysis compared the occurrence of each health outcome among individuals with prenatal and early childhood PCE exposure to unexposed individuals while considering the effect of confounding variables. Findings: The study found evidence that early-life exposure to PCE-contaminated drinking water has long-term neurotoxic effects. The strongest associations were seen with illicit drug use, bipolar disorder, and post-traumatic stress disorder. Key strengths of the study were availability of historical data on affected water systems, a relatively high exposure prevalence and wide range of exposure levels, and little confounding. Challenges arose mainly from the historical nature of the exposure assessments. Conclusions: The Cape Cod Health Study demonstrates how scientists can take advantage of unique “natural experiments” to learn about the health effects of environmental pollution. This body of work has improved our understanding of the long-term health effects of early-life exposure to this common environmental contaminant and will help risk assessors and policymakers ensure that drinking water supplies in the United States are safe for vulnerable populations.